The Implementation of the Posyandu Program and Complete Infant Immunization at the Tiga Balata Community Health Center - Wilson Samosir (International Journal of Public Health Excellence (IJPHE), 2023)
Posyandu activities throughout Indonesia are carried out once a month or more, where activities carried out by posyandu refer to the 5 table system. Completeness of infant immunization is the fulfillment of artificial active immunization required by the government, namely BCG, HBO, DPT/HB, Polio, and Measles. The research objective was to describe the implementation of the posyandu program and the completeness of infant immunization. This research is a descriptive explorative research. The study population was mothers with children aged 1-2 years who had come to posyandu in Kasindir Village, Jorlang Hataran District, Simalungun Regency, namely 70 people with a total sampling technique. However, those who were willing to be research respondents were 64 people. Data were analyzed descriptively with a computerized program. The implementation of the posyandu program in Jorlang Hataran District, Simalungun Regency, based on the research results, has gone well (90.6%), but there are still a number of activities that have not been fully implemented including the presence of doctors (26.6%), health counseling (29.7%) , facilities and infrastructure needed in the implementation of Posyandu (48.4%). For the completeness of infant immunization, most of them have received complete immunization, amounting to 85.9%. From the results of this study it is hoped that health workers at the Tiga Balata Health Center can maintain and increase the role of the posyandu for the community in their working area, and it is hoped that the puskesmas staff will increase their presence in every posyandu activity